The effect of intervening variable towards twin deficit in Indonesia: the application of path analysis - Erni Ummi Hasanah,; Sarungu, J.J; Mulyanto,; Soesilo, A.M; Suparjito, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study examines twin deficits in Indonesia during the period of 1969-2015 using Path Analysis. Path analysis can test the direct and indirect effect of the variables studied and simultaneously identify the role of the intervening variables. Data used in this study include government budget deficit (BD) as the exogenous variable, interest rate (IR) and domestic exchange rate (FER) as the endogenous intervening variables, and deficit on the current account of balance of payment (DBOP) as the endogenous variable. This study found no direct effect between BD and DBOP. The finding indicates that an increase in budget deficit may not necessarily lead to an increase in current account deficits, and therefore do not prove twin deficits in Indonesia. Therefore, Mundell-Fleming's theory in Indonesia is not applicable because the role of intervening variables (IR and FER) in mediating twin deficits is relatively weak.